2006
DOI: 10.1002/ejlt.200600061
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of fatty acid esters in subcritical water

Abstract: Hydrolysis of fatty acid esters in subcritical waterHydrolysis of esters of higher fatty acids by subcritical water, performed in a flowthrough tubular reactor, was investigated at temperatures from 280 up to 340 7C and pressures exceeding 12 MPa, using an ester/water ratio of 1 : 2 or 1 : 4 (vol/vol). The kinetics of the hydrolysis of both the triacylglycerols and the methyl esters obeyed the rate equation valid for first-order reactions. Conversion of the esters to free fatty acids exceeding 95% was reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 8 publications
1
29
0
Order By: Relevance
“…Dimerization of 21 38 fatty acids is also reported by Kocsisová, et al 38 This type of reaction applied to linoleic acid would be responsible for the formation of heavy species, undetectable by GC-MS.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Dimerization of 21 38 fatty acids is also reported by Kocsisová, et al 38 This type of reaction applied to linoleic acid would be responsible for the formation of heavy species, undetectable by GC-MS.…”
mentioning
confidence: 69%
“…It decomposes biomass and produces four valuable products: a crude-like bio-oil with higher heating values up to [35][36][37][38][39][40] À1 , a combustible solid residue called 'char', an aqueous phase containing light polar platform chemicals, and a CO 2 -rich gaseous phase also containing certain amounts of hydrogen and light hydrocarbons. Many resources are considered for HTL, such as sewage sludge, 2 food processing residues, 3 and algae.…”
mentioning
confidence: 99%
“…Furthermore, complete conversion is achieved in a relatively short time. Due to these advantages, several studies on the catalyst-free hydrolysis of vegetable oils using subcritical water have been conducted to produce FAs [13][14][15][16] However, severe reaction conditions of subcritical water have reportedly resulted in the decomposition of FAs during hydrolysis, consequently leading to low FA yield [14]. Therefore, preventing thermal degradation of FAs is one of the most important concerns in non-catalytic FA production.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a subcritical water, which can act as both solvent and reagent for the hydrolysis of triglyceride [183,188], has been proven to be effective for hydrolyzing soybean oil to free fatty acids resulting in rapid splitting of triglicerides at temperature range of 330 and 340 • C yielding 97% or higher conversion without the need of catalysts or emulsifying agents [184]. The subcritical water-assisted splitting was also reported -the conversion of the esters to free fatty acids exceeding 95% was achieved at 340 • C [189]. The application of IR study on the hydrolysis revealed structural changes in the chains of the unsaturated fatty acids and their partial polymerization during the hydrolysis.…”
Section: Fundamental Reactions Involving Watermentioning
confidence: 88%